Physical stress for overproduction of biomass and flavonoids in cell suspension cultures of boesenbergia rotunda - Yusuf, N.A.; Annuar, M.S.M.; Khalid, N. (2012)
Flavonoid, a bioactive compound isolated from the rhizomes of Boesenbergia rotunda, exhibited antibiotic and anti-inflammatory properties and has also shown high inhibitory activity of dengue-2 virus protease. Several factors are responsible for the production of flavonoid in cell cultures. In the present study, the effects of initial inoculation volume, temperature and speed of agitation on cell growth, total and selected flavonoid in suspension cultures of B. rotunda were determined. High performance liquid chromatography analysis showed that a 2 inoculation volume induced a significantly high accumulation of biomass and of flavonoid in the cells. The cells cultured at 25 °C showed significantly high biomass and selected flavonoid accumulation while differences in medium agitation significantly affected the yield of selected flavonoid.